Business Plan : Fertilized, Herbicide and Pesticide Trading Company / Mohamad Hafiz Faiq Hamzah ... [et al.] - Hamzah, Mohamad Hafiz Faiq; Ahmad Shukri, Ahmad Syafiq; Bashir, Mohd Hariz; Rosdi, Noor Amirah; Abu Bakar, Yasmin (2012)
This business is started with the cooperation and partnership of Mohd Hariz Bin Bashir, Ahmad Syafiq Bin Ahmad Shukri, Nor Amirah Bt Rosdi, Yasmin Bt Abu Bakar, And Hafiz Faiq B Hamzah. the name of our company is Shahy Agrotech, with each letter represent each one of our calling name. Shahy Agrotech is trading company that sells and supplies, and deliver fertilizer, pesticide, and herbicide, which is needed in the agriculture sector, mainly in palm oil sector to customer. demand is constant, stable, and high due to the ever increasing palm oil sector. we are a customer oriented company. we will try our utmost best to never say no to a customer. Our company consist of 5 positions on the general management to carry out office and general works. the five positions are general manager, operation manager, marketing manager, administration manager, and financial manager. our business will be operating at t16, kawasan perindustrian miel, teluk kalong, 24000, kemaman, terengganu. commencing of proposed business is on the 1st may of 2014. In serving the customer needs, we will do our best in order to satisfy our customer, in term of our pricing, service, and the choices of products in our inventory. we will personally deliver our customer order to their desired location, as soon as possible. since we start small, we can concentrate in a smaller area which is kemaman, thus enabling us to deliver our product within 1-3 working days at most. One of the factors that lew to the establishment of our company is because of the opportunity to expand since demand is constant, steady, and increasing. In conclusion, we hope that our customer will be satisfy with our products and service provided. in keeping with our customer oriented company theme, feedback and suggestion from the customers are always welcome to further improve our services, items, and company, to again, better service for our customer.